Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

help me find the two tables which represent quadratic relationships

Help Me Find The Two Tables Which Represent Quadratic Relationships class=

Sagot :

First, we can notice that all the optins have the same x values: 0, 1, 2 and 3.

These are at equal differences of 1.

A quadratic relationship has the property that the difference of the differences of subsequent points is constant.

So, to check wheter it is a quadratic relationship, we can calculate the differences between f(1) and f(0), f(2) and f(1) and f(3) and f(2):

[tex]\begin{gathered} f(1)-f(0) \\ f(2)-f(1) \\ f(3)-f(2) \end{gathered}[/tex]

And then we make the difference between the first and second differences and between the third and second. if they are equal and difference than 0, it is a quadratic relationship.

For the first, we have:

[tex]\begin{gathered} f(1)-f(0)=-8-(-4)=-8+4=-4 \\ f(2)-f(1)=-10-(-8)=-10+8=-2 \\ f(3)-f(2)=-10-(-10)=-10+10=0 \end{gathered}[/tex]

Now, the difference of differences:

[tex]\begin{gathered} -2-(-4)=-2+4=2 \\ 0-(-2)=2 \end{gathered}[/tex]

They are equal, so the first one is a quadratic relationship.

The second, we have:

[tex]\begin{gathered} f(1)-f(0)=0-(-2)=0+2=2 \\ f(2)-f(1)=2-0=2 \\ f(3)-f(2)=4-2=2 \end{gathered}[/tex]

Now, the difference of differences:

[tex]\begin{gathered} 2-2=0 \\ 2-2=0 \end{gathered}[/tex]

They are the same but they are equal to zero, so the second is not a quadratic relationship. This will happen when the first differences are constant, becaise this is a linear relationship. Notice that the fifth also have constant differences, so the fifth is not a quadratic relationship.

For the third, we have:

e have:

[tex]\begin{gathered} f(1)-f(0)=-4-4=-8 \\ f(2)-f(1)=-4-(-4)=-4+4=0 \\ f(3)-f(2)=4-(-4)=4+4=8 \end{gathered}[/tex]

Now, the difference of differences:

[tex]\begin{gathered} 0-(-8)=0+8=8 \\ 8-0=8 \end{gathered}[/tex]

They are equal so, the third is also a quadratic relationship.